Electrocatalytic Activity of Carbon Paste Electrode Modified with Porphyrin and SWCNT for Oxygen Reduction Reaction - Yin, Wei; Zhou, Han; Li, Qi; Lv, Shihuan; Liu, Xiaofei; Fa, Huanbao; Chen, Changguo (Asian Journal of Chemistry, 2015)
A carbon paste modified electrode (CPME) with 5,10,15,20-tetraphenylporphyrinato cobalt(II) (CoTPP) and single walled carbon nanotube (SWCNT) was prepared by simple, rapid and effective method. Its electrochemical catalytic behaviour for oxygen was investigated in oxygen-saturated 0.1 mol/L Na2HPO4-NaH2PO4 buffer solution (PBS) (pH 7). By using rotating disk electrode, the analysis was carried out that oxygen reduction on CP/CoTPP/SWCNT in 0.1 mol/L PBS (pH 7) is through two-electron pathway and the possible catalytic mechanism was discussed. The CPME was very stable and exhibited high tolerance to methanol. It is suggested that CoTPP and SWCNT modified carbon paste modified will offer a possibility of developing a sensitive method for the determination of dissolved oxygen.